Proposed Canadian Consensus Guidelines on Osteoarthritis Treatment Based on OA-COAST Stages 1–4 - Mosley, Conny; Edwards, Tara; Romano, Laura; Truchetti, Geoffrey; Dunbar, Laurie; Schiller, Teresa; Gibson, Tom; Bruce, Charles; Troncy, Eric (Frontiers in Veterinary Science, 2022)
The Canadian consensus guidelines on OA treatment were created from a diverse group of experts, with a strong clinical and/or academic background in treating OA in dogs. The document is a summary of the treatment recommendations made by the group, with treatments being divided into either a core or secondary recommendation. Each treatment or modality is then summarized in the context of available research based support and clinical experience, as the treatment of OA continues to be a multimodal and commonly a multidisciplinary as well as individualized approach. The guidelines aim to help clinicians by providing clear and clinically relevant information about treatment options based on COAST defined OA stages 1 - 4.